2014
DOI: 10.1002/2014jc010284
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of radar‐derived snow depth over Arctic sea ice

Abstract: Knowledge of contemporaneous snow depth on Arctic sea ice is important both to constrain the regional climatology and to improve the accuracy of satellite altimeter estimates of sea ice thickness. We assess new data available from the NASA Operation IceBridge snow radar instrument and derive snow depth estimates across the western Arctic ice pack using a novel methodology based on wavelet techniques that define the primary reflecting surfaces within the snow pack. We assign uncertainty to the snow depth estima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
83
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 66 publications
(87 citation statements)
references
References 33 publications
4
83
0
Order By: Relevance
“…Although the data in Fig. 6 represent level ice in the landing areas excluding local variations like sastrugi, the results are in agreement with other studies of in situ data (Sturm et al, 2006;Farrell et al, 2012;Newman et al, 2014) and data from IceBridge airborne surveys (Kurtz and Farrel, 2011;Kwok, 2017). It is noteworthy that the snow depth distribution in The Cryosphere Discuss., https://doi.org /10.5194/tc-2017-278 Manuscript under review for journal The Cryosphere Discussion started: 22 December 2017 c Author(s) 2017.…”
Section: Depth Of Undisturbed Snow Coversupporting
confidence: 90%
“…Although the data in Fig. 6 represent level ice in the landing areas excluding local variations like sastrugi, the results are in agreement with other studies of in situ data (Sturm et al, 2006;Farrell et al, 2012;Newman et al, 2014) and data from IceBridge airborne surveys (Kurtz and Farrel, 2011;Kwok, 2017). It is noteworthy that the snow depth distribution in The Cryosphere Discuss., https://doi.org /10.5194/tc-2017-278 Manuscript under review for journal The Cryosphere Discussion started: 22 December 2017 c Author(s) 2017.…”
Section: Depth Of Undisturbed Snow Coversupporting
confidence: 90%
“…We then discriminate between first year ice (FYI) and multiyear ice (MYI) to investigate whether f depends on the ice age. In general, MYI has a thicker snow layer than FYI [see, e.g., Newman et al, 2014], and we examine the claim of Kwok [2014] that the residual error due to snow pack scattering is larger for thicker snow depths.…”
Section: Discussionmentioning
confidence: 99%
“…The airborne data will be more sensitive to the presence of thinner ice floes that may be missed by the satellites (due to the large satellite footprint and rejection of complex waveforms [Wingham et al, 2006]), as well as pressure ridges. It has been shown recently that the OIB radar system is impacted by ice surface morphology, and estimating snow depth uncertainty over heavily deformed sea ice remains challenging [Newman et al, 2014]. Using a wavelet technique, Newman et al [2014] found that snow radar-derived snow depths over MYI were larger than in the OIB Sea Ice Freeboard, Thickness, and Snow Depth product by 1 cm and 4 cm in 2011 and 2012, respectively.…”
Section: 1002/2015gl064823mentioning
confidence: 99%
“…The Wavelet algorithm, described by Newman et al (2014), operates on each trace (column) of an echogram independently and has three components: interface detection through the use of the Haar wavelet-continuous wavelet transform (Haar-CWT), topographic filtering using the h topo parameter (to mitigate against heavily deformed ice topography on the radar point of closest approach), and the assignment of precision to each derived snow depth using radar system parameters.…”
Section: Waveletmentioning
confidence: 99%